Body weight in mouse embryos specifies staging of tooth development - Peterka, M; Lesot, H; Peterková, R (Connective tissue research, 2002)
Great intra- and interlitter variation in morphological stages is known to exist among mouse embryos of the same strain at a similar chronological stage. With the aim of searching for an easily measurable parameter that correlates well with tooth development, the morpho- and histodifferentiation of teeth were compared in embryos classified according to the embryonic day (ED) specified by wet body weight. The embryos and fetuses were harvested at 12-h intervals from ED12.5 until birth, weighed, fixed, and processed histologically. The tooth age was determined according to the developmental progress of the first molar, evaluated based on morpho- and histodifferentiation criteria. The data documented a better correlation between tooth morpho-histodifferentiation with the age/weight staging than with only the embryonic day. The cyto-differentiation of odontoblasts exhibited a high interlitter variability and was similar within specimens of the same litter, regardless of their body weight differences.
Keywords: Odontoblasts; Body Weight; Embryonic and Fetal Development; myši; myši inbrední ICR; odontogeneze; Mice, Inbred ICR; embryo savčí; Embryo, Mammalian; odontoblasty; Animals; Mice; embryonální a fetální vývoj; tělesná hmotnost; Odontogenesis; zvířata